Computer-Assisted Design and Computer-Assisted Modeling Technique Optimization and Advantages Over Traditional Methods of Osseous Flap Reconstruction - Matros, Evan; Albornoz, Claudia R.; Rensberger, Michael; Weimer, Katherine; Garfein, Evan S. (Journal of Reconstructive Microsurgery, 2014)
There is increased clinical use of computer-assisted design (CAD) and computer-assisted modeling (CAM) for osseous flap reconstruction, particularly in the head and neck region. Limited information exists about methods to optimize the application of this new technology and for cases in which it may be advantageous over existing methods of osseous flap shaping. A consecutive series of osseous reconstructions planned with CAD/CAM over the past 5 years was analyzed. Conceptual considerations and refinements in the CAD/CAM process were evaluated. A total of 48 reconstructions were performed using CAD/CAM. The majority of cases were performed for head and neck tumor reconstruction or related complications whereas the remainder (4%) were performed for penetrating trauma. Defect location was the mandible (85%), maxilla (12.5%), and pelvis (2%). Reconstruction was performed immediately in 73% of the cases and delayed in 27% of the cases. The mean number of osseous flap bone segments used in reconstruction was 2.41. Areas of optimization include the following: mandible cutting guide placement, osteotomy creation, alternative planning, and saw blade optimization. Identified benefits of CAD/CAM over current techniques include the following: delayed timing, anterior mandible defects, specimen distortion, osteotomy creation in three dimensions, osteotomy junction overlap, plate adaptation, and maxillary reconstruction. Experience with CAD/CAM for osseous reconstruction has identified tools for technique optimization and cases where this technology may prove beneficial over existing methods. Knowledge of these facts may contribute to improved use and main-stream adoption of CAD/CAM virtual surgical planning by reconstructive surgeons.
Keywords: head and neck; reconstruction; CAD/CAM; computer-assisted design; computer-assisted modeling